2013
DOI: 10.1093/toxsci/kft162
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Dioxide and Ultrafine Particles Dominate the Biological Effects of Inhaled Diesel Exhaust Treated by a Catalyzed Diesel Particulate Filter

Abstract: We studied the impact of a catalyzed diesel particulate filter (DPF) on the toxicity of diesel exhaust. Rats inhaled exhaust from a Cummins ISM heavy-duty diesel engine, with and without DPF after-treatment, or HEPA-filtered air for 4h, on 1 day (single exposure) and 3 days (repeated exposures). Biological effects were assessed after 2h (single exposure) and 20h (single and repeated exposures) recovery in clean air. Concentrations of pollutants were (1) untreated exhaust (-DPF), nitric oxide (NO), 43 ppm; nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 45 publications
5
19
0
2
Order By: Relevance
“…The modeled leptin was obtained from the respective 3D Gaussian non-linear correlation of age and the observed BMI and leptin levels (R 2 ¼0.56) in southwest Mexico City. neuroinflammatory changes seen in exposed urbanites (Thomson et al, 2007;Karthikevan et al, 2013). ET-1 blood levels alter key regulatory mechanisms of the cerebral circulation by modulating endothelial NO synthase phosphorylation and NO production through Rho-associated protein kinase (Faraco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The modeled leptin was obtained from the respective 3D Gaussian non-linear correlation of age and the observed BMI and leptin levels (R 2 ¼0.56) in southwest Mexico City. neuroinflammatory changes seen in exposed urbanites (Thomson et al, 2007;Karthikevan et al, 2013). ET-1 blood levels alter key regulatory mechanisms of the cerebral circulation by modulating endothelial NO synthase phosphorylation and NO production through Rho-associated protein kinase (Faraco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hepatic NFκB, plasma TNFα, and IL‐6 as well as plasma ALT and AST were increased at 1 month in this study. Karthikeyan et al () investigated the biological effects of diesel exhaust on lung of Fischer‐344 male rats and reported that not only nanoparticles but also NO 2 in diesel exhaust induced acute inflammation in the lung. Therefore, the effects of NO 2 may not be denied in NR‐DE‐induced hepatic inflammation observed in the present study, although the concentrations were much lower than in the Karthikeyan study.…”
Section: Discussionmentioning
confidence: 99%
“…Cleansing technologies, such as diesel exhaust particle filters (DPF) reduce the particle mass emitted, and result in emission of smaller particulates (Hawley et al, 2014;Karthikeyan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%